ANALISA FAKTOR PENUNJANG DAN PENGHAMBAT DALAM PENGEMBANGAN KECERDASAN MORAL ANAK USIA DINI 5-6 TAHUN - Lely Fajriyah; Andre Depeda; Rina Puspita Sari (Nusantara Hasana Journal, 2022)
Moral intelligence is the ability to understand what is right and what is wrong, have strong ethical beliefs and act. This very important intelligence includes the main characters, such as the ability to understand the suffering of others and not act maliciously, being able to control impulses and delay gratification, listening from various parties before making judgments, accepting and respecting differences, being able to understand unethical choices, can empathize, fight for justice, and show compassion and respect for others. Purpose To determine the factors supporting and inhibiting the moral intelligence of children aged 5-6 years. The research method uses a qualitative research approach, and uses a library research method. The analysis is a descriptive analysis, so as to produce descriptive data. Conclusion The moral condition of children's religion, with the inculcation of moral values, children can behave politely towards their friends and class teachers, children are also honest, mutual respect for teachers and friends during the teaching and learning process in class.